Carbonation resistance of concrete with fly ash as fine aggregate - Zhang, D.; Mao, M.; Yang, Q.; Lim, Kar Sing (2019)
In order to investigate the carbonation resistance of concrete with fly ash as fine aggregate (CFA), the rapid carbonation test was conducted to explore the influence of the curing age, water-to-cement (w/c) ratio, fly ash replacement rate and the activator on the carbonation depth. The experimental results show that prolonging the curing time is beneficial to improving the carbonation resistance of the CFA. The carbonation depth of the CFA correlates positively with the w/c ratio. With an increase in the fly ash replacement rate and w/c ratio, the carbonation resistance of the CFA increases to a remarkable extent. After 28 days of standard maintenance of the CFA, the compactness of the CFA is boosted due to the pozzolanic effect of the fly ash, and its carbonation resistance is enhanced compared to that of ordinary concrete. In addition, the incorporation of the activator marginally contributes to the improvement of the carbonation resistance of the CFA.